2011
DOI: 10.1103/physrevb.83.064202
|View full text |Cite
|
Sign up to set email alerts
|

Exchange between interstitial oxygen molecules and network oxygen atoms in amorphousSiO2studied byO18

Abstract: Amorphous SiO 2 (a-SiO 2) thermally annealed in an oxygen atmosphere incorporates oxygen molecules (O 2) in interstitial voids. When the thermal annealing is performed in 18 O 2 gas, interstitial 18 O 2 as well as interstitial 16 O 18 O and 16 O 2 are formed due to the oxygen exchange with the a-SiO 2 network. The a 1 g (v = 0) → X 3 − g (v = 1) infrared photoluminescence band of interstitial O 2 was utilized to quantitatively analyze the oxygen exchange, taking into account the influences of common network mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…A prominent role of amorphous structure and density of the material has been put forward both by experimental and simulative works, suggesting that higher material density inhibits molecule diffusion. , Furthermore, it has been shown that diffusion of the O 2 can occur without interaction with the network oxygen or by contrast with a molecule–network exchange of atoms. , This latter process is negligible below 900 °C where the exchange-free diffusion length reaches values of ∼1 μm. As a final concern, it has been evidenced that network modifiers could have minor effects on the O 2 migration, and the more relevant species could be SiOH through a dehydroxylation process, causing an interstitial water driven exchange of oxygen with the SiO 2 network at high temperatures. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prominent role of amorphous structure and density of the material has been put forward both by experimental and simulative works, suggesting that higher material density inhibits molecule diffusion. , Furthermore, it has been shown that diffusion of the O 2 can occur without interaction with the network oxygen or by contrast with a molecule–network exchange of atoms. , This latter process is negligible below 900 °C where the exchange-free diffusion length reaches values of ∼1 μm. As a final concern, it has been evidenced that network modifiers could have minor effects on the O 2 migration, and the more relevant species could be SiOH through a dehydroxylation process, causing an interstitial water driven exchange of oxygen with the SiO 2 network at high temperatures. , …”
Section: Introductionmentioning
confidence: 99%
“…As a final concern, it has been evidenced that network modifiers could have minor effects on the O 2 migration, and the more relevant species could be SiOH through a dehydroxylation process, causing an interstitial water driven exchange of oxygen with the SiO 2 network at high temperatures. 26,27 The precedent studies have been typically carried out at temperatures above 500 °C due to a limitation in the detectability of the O 2 in bulk systems caused by the low penetration. Studies at lower temperature and in nanodimensional silica are limited and deserve to be done in view of the above-mentioned applications at the nanoscale.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Comparison between eq and the initial decay of f * shown in Figure yielded a k F value of ∼4 × 10 –24 cm 5 J –1 . The exchange rate per second ( k F F at F = 20 mJ cm –2 ) was ∼8 × 10 –26 cm 3 s –1 , which is of approximately equal magnitude as the rate of thermal oxygen exchange at 700 °C in this type of glass (∼1 × 10 –25 cm 3 s –1 ).…”
Section: Resultsmentioning
confidence: 82%
“…The 18 O fraction of interstitial O 2 , f *, decreased monotonically with F 2 laser fluence, F . The decrease in f * was due to the supply of 16 O from the Si–O–Si network , normalO 18 normalO 18 + ≡Si− normalO 16 −Si≡ normalO 16 normalO 18 + ≡Si− normalO 18 −Si≡ normalO 16 normalO 18 + ≡Si− normalO 16 −Si≡ normalO 16 normalO 16 + ≡Si− normalO 18 −Si≡ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation